Periodontitis is associated with endothelial dysfunction in a general population: a cross-sectional study. - Birte Holtfreter (Public Library of Science (PLoS), 2013)
A large body of evidence underlines an association between periodontal disease and cardiovascular disease. In contrast, data on its relation with endothelial dysfunction as a marker of early subclinical atherosclerosis is inconclusive and limited to patient-cohort studies. We therefore investigated the association between periodontal disease and flow-mediated dilation of the brachial artery (FMD) as a measure of endothelial dysfunction in a general population, and also addressed a possible mediation via inflammation. The study population comprised 1,234 subjects (50.5% men) aged 25-85 years from the 5-year follow-up of the Study of Health in Pomerania, a population-based cohort study. Clinical attachment loss (CAL) and pocket probing depth (PPD) as measures of periodontal disease were assessed half-mouth at four sites per tooth. Subjects were classified according to the periodontitis case definition proposed by Tonetti and Claffey (2005). Measurements of FMD and nitroglycerin-mediated dilation (NMD) were performed using standardized ultrasound techniques. High-sensitive C-reactive protein, fibrinogen and leukocyte count were measured. Fully adjusted multivariate linear regression analyses revealed significant associations of the percentage of sites with PPD ≥ 6 mm with FMD (p(trend)=0.048), with subjects within the highest category having a 0.74% higher FMD compared to subjects within the lowest category (p<0.05). Consistently, FMD values increased significantly across categories of the percentage of sites with CAL ≥ 6 mm (p(trend)=0.01) and the periodontitis case definition (p(trend)=0.006). Restrictions to subjects without antihypertensive or statin medication or current non-smokers confirmed previous results. Systemic inflammation did not seem to mediate the relation. Both PPD and CAL were not consistently associated with NMD. In contrast to previous studies, high levels of periodontal disease were significantly associated with high FMD values. This association was not mediated via systemic inflammation. This study revives the discussion on whether and how periodontitis contributes to endothelial dysfunction.